Hepatotoxicity of the Major Anthraquinones Derived From Polygoni Multiflori Radix Based on Bile Acid Homeostasis - Kang, Li; Li, Dan; Jiang, Xin; Zhang, Yao; Pan, Minhong; Hu, Yixin; Si, Luqin; Zhang, Yongjun; Huang, Jiangeng (Frontiers in Pharmacology, 2022)
Polygoni Multiflori Radix (PMR), the dried root of Polygonum Multiflorum Thumb., has been widely used as traditional Chinese medicines in clinical practice for centuries. However, the frequently reported hepatotoxic adverse effects hindered its safe use in clinical practice. This study aims to explore the hepatotoxic effect of PMR extract and the major PMR derived anthraquinones including emodin, chrysophanol and physcion in mice and the underlying mechanisms based on bile acids homeostasis. After consecutively treating the ICR mice with PMR extract or individual anthraquinones for 14 or 28 days, the liver function was evaluated by measuring serum enzymes levels and liver histological examination. The compositions of bile acids (BAs) in bile, liver and plasma were measured by LC-MS/MS, followed by Principal Component Analysis (PCA) and Partial Least Squares Discriminate Analysis (PLS-DA). Additionally, gene and protein expression of BA efflux transporters, bile salt export pump (Bsep) and multidrug resistance-associated protein 2 (Mrp2), were examined to investigate the underlying mechanisms. After 14-day administration, mild inflammatory cell infiltration in liver was observed in the physcion- and PMR-treated groups, while it was found in all the treated groups after 28-day treatment. Physcion and PMR extract induced hepatic BAs accumulation after 14-day treatment, but such accumulation was attenuated after 28-day treatment. Based on the PLS-DA results, physcion- and PMR-treated groups were partially overlapping and both groups showed a clear separation with the control group in mouse liver. The expression of Bsep and Mrp2 in physcion- and PMR-treated mouse liver was decreased after 14-day treatment, while the downregulation was abrogated after 28-day treatment. Our study for the first time demonstrated that both PMR extract and tested anthraquinones could alter the disposition of either the total or individual BAs in mouse bile, liver and plasma via regulating the BAs efflux transporters and induce liver injury, which provide a theoretical basis for the quality control and safe use of PMR in practice.